Evaluating the effect of different conditioning agents on the shear bond strength of resin-modified glass ionomers - Namith Rai; Rajaram Naik; Ravi Gupta; Shobana Shetty; Amith Singh (Wolters Kluwer Medknow Publications, 2017)
Aim of the Study: This study aims to evaluate the effects three different conditioning agents on the shear bond strength of resin-modified glass ionomers to human dentin. Materials and Methods: One hundred and twenty recently extracted, caries-free premolars and molars will be cleaned of debris and disinfected in a 0.5% solution of sodium hypochlorite and sterile water for 30 min. The occlusal surface of each tooth will be reduced using conventional model trimmer with water to produce the dentin surface. Then, three different resin-modified glass ionomer cements (GICs) were triturated and mixed according to the manufacturer's instructions, 10 specimens will be made of each group. The excess restorative material will be removed from matrix band dentin interface with a sharp number 25 bard parker blade. Samples were shear tested with Instron universal testing machine with a crosshead speed of 0.5 mm/min. A shearing bar beveled to a 1 mm thick contact surface area will be placed at the junction of dentin and plastic band matrix. The load required for the failure will be recorded in pounds and converted to megapascals. Results: Statistical analysis was done with analysis of variance and Tukey's test. Ketac primer as conditioning agent along with Fuji II LC as restorative material had the highest shear bond value whereas intact smear layer which was unmodified dentin had the least value. Conclusion: Within the limitations of the present study, it can be concluded that surface conditioning of dentin resulted significantly higher bond strength than unconditioned dentin surfaces. Clinical Significance: Resin-modified glass ionomers have several advantages compared to chemically cured GICs. The advantages include command cure, ease of handling, improved physical properties, and esthetics. Resin-modified glass ionomers have been marketed as direct restorative materials for Class V lesions as well as liners, bases, and luting agents. Several conditioning agents have been evaluated to condition dentin before the application of conventional glass ionomers and resin-modified glass ionomers. These have mainly included polyacrylic acid, citric acid, phosphoric acid, and ethylenediamine tetra-acetic acid. Of late, manufactures have recommended other conditioners to replace polyacrylic acid which includes Ketac primer as one of the conditioning agents.